2020
DOI: 10.26833/ijeg.580027
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of ambiguity resolution on PPP and relative positioning techniques: consideration of satellite geometry

Abstract: Ambiguity resolution plays an important role in surveying using Precise Point Positioning (PPP) and relative positioning techniques that require high accuracy. In this study, ambiguity resolution performance of PPP and relative positioning under the unobstructed (with 7° cut-off angle) and constrained environment (with 25° cut-off angle, such as nearby buildings and street-canyons) using final/ultra-rapid orbit and clock products are investigated for different observation time. Seventeen globally distributed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It can also be observed that the LAMBDA method leads the slight accuracy degradation with daily data for the 7° cutoff angle. It is related that some ambiguities that belong to the identical epoch time could not be fixed correctly by the LAMBDA method (Ogutcu 2020). When the RMSEs were computed without the outlier removal, accuracy improvement in all coordinate components with respect to the float solution was seen for the LAMBDA method.…”
Section: Results and Analysismentioning
confidence: 98%
“…It can also be observed that the LAMBDA method leads the slight accuracy degradation with daily data for the 7° cutoff angle. It is related that some ambiguities that belong to the identical epoch time could not be fixed correctly by the LAMBDA method (Ogutcu 2020). When the RMSEs were computed without the outlier removal, accuracy improvement in all coordinate components with respect to the float solution was seen for the LAMBDA method.…”
Section: Results and Analysismentioning
confidence: 98%
“…In recent years, a lot of research has developed in this methodology to verify the possibilities of both static and kinematic multi-constellation measurements and to improve the convergence of PPP solutions. (Bulbul et al, 2021;Ogutcu, 2020;Angrisano et al, 2020;Li et al, 2015;Anquela et al, 2013). GNSS technology is therefore a useful and fundamental tool in various fields, including precision positioning and navigation, continually presenting new challenges to both researchers and device manufacturers and suppliers (Huang et al, 2023;Gonzalez and Dabove, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has become very popular in the scientific world as a very cost-effective technique [10][11][12][13]. The effectiveness of the traditional-PPP technique has been proven in many applications such as characterization of seismic waveforms, structural health monitoring, GNSS buoy, precise orbit determination of low orbit satellites and determination of position of moving objects [14][15][16][17][18][19][20][21]. Furthermore, the performance of determining permanent deformations of the traditional-PPP technique has also been examined [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%